Comparing effects of breathing exercises alone and combined with breathing-stretching exercises on respiratory indices, disease severity and exercise capacity in COPD - Fatemeh Zare; Mahdi Karimyar Jahromi; Zhila Rahmanian; Mohsen Faseleh Jahromi (Scientific Reports, 2025)
Abstract No study has ever comprehensively investigated the effect of rehabilitation exercises on patients with chronic obstructive pulmonary disease, taking into account different aspects. The present study was conducted to compare effects of breathing exercises alone and combined with breathing-stretching exercises on respiratory indices, disease severity and exercise capacity in COPD. This randomized clinical trial was conducted at Jahrom University of Medical Sciences in May–July, 2024. The research population included 32 COPD patients who were randomly divided into control (routine breathing exercises) and intervention (combined routine breathing and breathing-stretching exercises) groups using convenience sampling method. Training was performed twice a day for five days. The used tools included COPD assessment test, 6-Minute Walk Test, venous blood gas and pulse oximeter. The data were analyzed using SPSS 25.0 and Shapiro-wilk test, Chi-square test, independent t-test and paired t-test. The results showed a statistically difference in the mean PCO2, O2sat, severity and 6MWT scores before and after the intervention in both groups (P-value < 0.05). Pco2 and severity reduction and O2sat and 6MWT increased in intervention group was more significant related to control group. Combined routine breathing and breathing-stretching exercises, compared to improved COPD patients’ respiratory indices, reduced disease severity and increased exercise capacity, more than using breathing exercises alone. Trial registration IRCT20240502061629N1, 08.05.2024 (available www.irct.behdasht.gov.ir).